Perceptual cues in the regulation of exercise performance – physical sensations of exercise and awareness of effort interact as separate cues. Issue 1 (26th September 2011) - Swart, Jeroen; Lindsay, Timothy Robert; Lambert, Michael Ian; Brown, James Craig; Noakes, Timothy David
Abstract : It has been argued that the physical sensations induced by exercise, measured as the ratings of perceived exertion (RPE), are distinct from the sense of effort. This study aimed to determine whether a new measure of task effort – the Task Effort and Awareness (TEA) score – is able to measure sensations distinct from those included in the conventional RPE scale. Seven well-trained cyclists completed a maximal effort 100 km time trial (TT) and a submaximal trial at 70% of the power sustained during the TT (70% TT). Five maximal 1 km sprints were included in both trials. Both the RPE related solely to physical sensation (P-RPE) and the TEA score increased during the TT and were linearly related. During the 70% TT, both P-RPE and TEA scores increased, but TEA increased significantly less than P-RPE (p<0.001). TEA scores reached maximal values in all 1 km sprints in both the maximal TT and 70% TT, whereas the RPE increased progressively, reaching a maximal value only in the final 1 km sprints in both the TT and the 70% TT. These results indicate that the physical sensations of effort measured as the P-RPE act as the template regulating performance during exercise and that deviation from that template produces an increase in the sense of effort measured by the TEA score. Together, these controls ensure that the chosen exercise intensity does not threaten bodily homeostasis. Our findings also explain why submaximal exercise conducted within the constraints of the template P-RPE does not produce any conscious awareness of effort.